2021
DOI: 10.3390/ijms22084262
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Alcohol Use Disorder (AUD). Genetics, Epigenetics, and Nutrition in AUD: An Amazing Triangle

Abstract: Alcohol use disorder (AUD) is a very common and complex disease, as alcohol is the most widely used addictive drug in the world. This disorder has an enormous impact on public health and social and private life, and it generates a huge number of social costs. Alcohol use stimulates hypothalamic–pituitary–adrenal (HPA) axis responses and is the cause of many physical and social problems (especially liver disease and cancer), accidental injury, and risky sexual behavior. For years, researchers have been trying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 173 publications
0
11
0
Order By: Relevance
“…Such metabolites are the products that result from the oxidation of alcohol by the cytoplasmic alcohol dehydrogenase (ALDH) enzyme, which, in general, is overexpressed in chronic ethanol consumption, followed by acetaldehyde dehydrogenase (ALDH), respectively, inducing toxicological liver effects and displaying hepatic fibrosis by a harmful feedback cycle, i.e., detrimental extra-cellular matrix remodeling, oxidative stress, and pro-inflammatory events [ 58 , 59 ]. All of these toxicological events occur as a result of blood alcohol concentration; however, they can persist during long-term withdrawal [ 23 ].…”
Section: Body Systems Consequences Of Ketamine Plus Ethanol Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Such metabolites are the products that result from the oxidation of alcohol by the cytoplasmic alcohol dehydrogenase (ALDH) enzyme, which, in general, is overexpressed in chronic ethanol consumption, followed by acetaldehyde dehydrogenase (ALDH), respectively, inducing toxicological liver effects and displaying hepatic fibrosis by a harmful feedback cycle, i.e., detrimental extra-cellular matrix remodeling, oxidative stress, and pro-inflammatory events [ 58 , 59 ]. All of these toxicological events occur as a result of blood alcohol concentration; however, they can persist during long-term withdrawal [ 23 ].…”
Section: Body Systems Consequences Of Ketamine Plus Ethanol Abusementioning
confidence: 99%
“…Several and robust preclinical and clinical studies have described the hazardous effects elicited by alcohol consumption, even after long-lasting withdrawal [ 20 , 21 , 22 , 23 ]. On the other side, ketamine non-medical purpose use has been described in only a few studies in the last decades [ 12 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the multiple signaling pathways that contribute to the pathogenesis of ALD, epigenetic alterations induced by alcohol have recently received much attention. Many studies have reported that hepatic epigenetic alterations by ethanol include DNA methylation, histone acetylation or methylation, and miRNA as post‐transcriptional modifiers (Dulman et al, 2020; Hardy & Mann, 2016; Siomek‐Gorecka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use disorder (AUD) is complex psychiatric disorder that is characterized by excessive alcohol drinking, alcohol dependence and relapses even after long periods of abstinence ( Siomek-Gorecka et al, 2021 ). It is a devastating public health problem and according to a WHO Global status report on alcohol and health in 2018, harmful use of alcohol resulted in about three million deaths worldwide in 2016 ( World Health Organization, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol and other drugs of abuse have been shown to change the synaptic plasticity and function of neurons in specific brain regions, resulting in long term changes at molecular, cellular and behavioural level ( Berkel and Pandey, 2017 ). It has been shown that during the development of AUD, both genetic and environmental factors play an important role ( Siomek-Gorecka et al, 2021 ). The fact that alcoholism tends to run in families has long been known and almost all twin studies have shown that heritability in AUD ranges from 40 to 60% ( Ducci and Goldman, 2008 ; Verhulst et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%